(3GdLhOI GdTGedI h JMbjb GdQbGHI aj GdHfhc GdJLGQjIs - (3eMeO SejQ(B, (3CMeOs ((3YeGf(B:s (3OGQ GdeSjQI ddfTQ hGdJhRjY(B,s, 2009)
(3GdQbGHI GdOGNdjI aj GdHfhc GdJLGQjI h ebheGJ h aGYdjI gPg GdQbGHI , GdYdGbI Hjf GdLhOI GdTGedI h GdQbGHI GdOGNdjI , eSDhdjI GdDbGHI GdOGNdjI aj JMbjb fXGe GdLhOI GdTGedI , Jbjje GdQbGHI GdOGNdjI h GdbOQI GdJfGaSjI aj GdHfhc GdJLGQjI , OQGSI JMdjdjI dJWHjb GdeTJbGJs
(3GdeQGLY U(B.197 ((3GbJfGAGJ (B2014 3(3f(B)s
Keywords: (3GdHfhc GdJLGQjIs; (3GdQbGHI GdeGdjIs; (3VHW GdLhOIs